Applicability of the linear–quadratic model to single and fractionated radiotherapy schedules: an experimental study - Miyakawa, Akifumi (Oxford University Press, 2014)
The aim of this study was to examine the applicability of the linear-quadratic (LQ) model to single and fractionated irradiation in EMT6 cells. First, the α/β ratio of the cells was determined from single-dose experiments, and a biologically effective dose (BED) for 20 Gy in 10 fractions (fr) was calculated. Fractional doses yielding the same BED were calculated for 1-, 2-, 3-, 4-, 5-, 7-, 15- and 20-fraction irradiation using LQ formalism, and then irradiation with these schedules was actually given. Cell survival was determined by a standard colony assay. Differences in cell survival between pairs of groups were compared by t-test. The α/β ratio of the cells was 3.18 Gy, and 20 Gy in 10 fr corresponded to a BED(3.18) of 32.6 Gy. The effects of 7-, 15- and 20-fraction irradiation with a BED(3.18) of 32.6 Gy were similar to those of the 10-fraction irradiation, while the effects of 1- to 5-fraction irradiation were lower. In this cell line, the LQ model was considered applicable to 7- to 20-fraction irradiation or doses per fraction of 2.57 Gy or smaller. The LQ model might be applicable in the dose range below the α/β ratio.